PENGARUH SUHU INLET TERHADAP EFISIENSI ENKAPSULASI Lactobacillus casei DALAM MIKROPARTIKEL (Dengan Matriks Kombinasi Kopolimer Asam Metakrilat Tipe L dan Tipe S serta Laju Alir Bahan 10 ml/menit) - ASTRID FEBRINA SAIMORA, 051511133214 (2019)
Lactobacillus casei is a probiotic that provides health benefit for human being by improving intestinal microbial balance if it’s taken as much as 106 – 109 cfu/g. Drug delivery system like microparticle is needed to protect Lactobacillus casei from gastric condition so it can release the probiotics in intestine. A matrix that is resistance to acid condition and dissolves in base condition is needed to protect Lactobacillus casei in the microparticle. The combination of methacrylic acid copolymer L-type and S-type is used as matrix in this research. The aim of this research is to know the effect of inlet temperature to encapsulation efficiency Lactobacillus casei in microparticle with a combination of methacrylic acid copolymer Ltype and S-type as a matrix. Microparticles were made by spray dry method with inlet temperature 100, 120, and 140 oC and feed flow rate 10 ml/min. The encapsulation effiency test was done after the microparticles were obtained. The encapsulation effiency at each inlet temperature were 25,93%; 24,65%; and 25,10%, respectively. The statistic analysis One Way ANOVA was done and the result showed that no significant difference was found on the encapsulation efficiencies of the three inlet temperatures.